(Invited) More Than Moore Applications with Thin-Film-Transistors Array Substrates from Liquid Cristal Display: New Devices for Biological Cells Analyses. (25th April 2016) - Tixier-Mita, Agnes; Ihida, Satoshi; Cathcart, Grant Alexander; Shaik, Faruk Azam; Toshiyoshi, Hiroshi
Abstract : Thin film transistor technology, mainly applied to liquid cristal displays, is used in this article for a new application, in a "More than Moore" objective, proposing new and unique solutions in the biomedical field. The devices fabricated with that technology are electrically controllable transparent substrates, perfectly suitable to build advanced systems for biological cells purposes. In addition, the transistor array, initially used as simple switches to control the pixels ON and OFF state of TFT-LCD, becomes an active part in the device, allowing not only DC or AC signal application, but also sensing, either through the microelectrodes, or directly being themselves a possible array of ISFETs. This article presents the results obtained until now by our group, which demonstrate the potential of such technology in the frame of biological cells research.